Bioinformatics characterization of variants of uncertain significance in pediatric sensorineural hearing loss - Clay, Sloane; Evans, Adele; Zambrano, Regina; Otohinoyi, David; Hicks, Chindo; Tsien, Fern (Frontiers in Pediatrics, 2024)
Rapid advancements in Next Generation Sequencing (NGS) and bioinformatics tools have allowed physicians to obtain genetic testing results in a more rapid, cost-effective, and comprehensive manner than ever before. Around 50% of pediatric sensorineural hearing loss (SNHL) cases are due to a genetic etiology, thus physicians regularly utilize targeted sequencing panels that identify variants in genes related to SNHL. These panels allow for early detection of pathogenic variants which allows physicians to provide anticipatory guidance to families. Molecular testing does not always reveal a clear etiology due to the presence of multigenic variants with varying classifications. This study aims to perform a preliminary bioinformatics characterization of patients with multigenic variants associated with Type II Usher Syndrome and provide an interpretation algorithm for physicians reviewing molecular results with medical geneticists.